IMPLEMENTATION OF THE BALANCED SCORECARD MODEL IN LOCAL SELF-GOVERNMENT AUTHORITIES - ORLIV, Mariana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Relevance of the study is due to the need to implement tools of strategic municipal management in local self-government authorities in order to successfully complete the reform of decentralization. Foreign experience testifies that one such tool is the Balanced Scorecard (BSC) of Kaplan and Norton, which was evolved from a performance management tool for business to a dominant system of strategic management in the public setor. This tool allows use of non-financial indicators, take into account social aspects and environment as well as manage risks under uncertainty.The article argues that the BSC implementation in local self-government authorities will ensure the solution of the following tasks: 1) aligning the strategic and tactical goals with measures for their implementation; 2) increasing the institutional capacity of authorities (through development and motivation of personnel, formation of innovative organizational culture, introduction of performance management system, improvement of internal processes, development of information systems); 3) increasing the transparency and stakeholders confidence, in particular foreign investors, to attract financing in the post-war period. It was found that the structure of the BSC model and the algorithm of its implementation depend on the field of activity, size, tasks and features of the organization. An algorithm for developing the BSC model of the city council executive committee (its structural unit for the pilot project implementation) is proposed and the main strategies for the four components of this model (stakeholders, finance, internal processes, training and development) are identified. Based on the experience of Canada, Denmark, the Czech Republic and other countries, the main advantages, conditions of success and challenges of implementing the BSC concept in local self-government authorities are identified, taking into account political, organizational, financial and other aspects. It is proposed to define the ways to solve considered challenges using the design thinking methodology.
Keywords: Balanced Scorecard; local self-government authorities; strategic management; performance management; institutional capacity